Finding the optimal background subtraction algorithm for EuroHockey 2015 video - Higham, D.; Kelley, J.; Hudson, C.; Goodwill, S. R. (Procedia Engineering, 2016)
Background subtraction is a classic step in a vision-based localization and tracking workflow. Previous studies have compared background subtraction algorithms on publicly available datasets; however comparisons were made only with manually optimized parameters. The aim of this research was to identify the optimal background subtraction algorithm for a set of field hockey videos captured at EuroHockey 2015.